Kayaking. - Dillon, Pamela S., ....-; Oyen, Jeremy, ....- (Champaign : Human Kinetics, 2009)
Embrace the outdoors by becoming one of the 17 million people who participate in kayaking, one of the fastest-growing outdoor activities around. Kayaking presents the basics of the sport as well as the skills and knowledge required for becoming a successful paddler. Expert instructors from the American Canoe Association provide you with * practical guidance on gear and equipment selection, nutrition, fitness and stretching, water trail etiquette, and safety and survival skills; * step-by-step paddling techniques for flatwater, river and whitewater, and sea kayaking, as well as instruction on more complex maneuvers and rolls; * useful consumer, technique, and safety tips throughout the book; * Web-based resources to help you plan trips throughout the world and find paddling organizations and instructors. Part I of Kayaking explains the background knowledge, fitness fundamentals, equipment and gear selection, nutritional needs, and safety and survival skills for a successful
Adventure. Part II helps build basic techniques, strokes, and maneuvers so you can embark on adventures of increasing difficulty. You'll find tips and instruction for the three most popular types of kayaking: sea, river, and whitewater. This book also includes the Quick-Start Your Kayak DVD to reinforce the paddling strokes and safety information found in the book. It features videos of kayaking maneuvers, which will make anyone capable of learning the basics. This introductory book teaches you the techniques and skills you need in order to enjoy your water adventure and then challenges those skills with more complex rolls and maneuvers. After reading Kayaking, you'll feel confident enough with your kayaking skills to test more challenging waterways and even plan overnight or extended trips with friends and family. Kayaking is part of the Outdoor Adventures series. This practical series contains the essential information to help you get ready and go. The books in this series will prepare
You with instruction in the basic techniques and skills so you can be on your way to an adventure in no time
Inhoudsopgave : Part I Preparing for a Kayaking Adventure Chapter 1. Going Kayaking Chapter 2. Getting Fit for Kayaking Chapter 3. Kayaks, Paddles, and Gear Chapter 4. Getting Ready to Kayak Chapter 5. Water Safety and Survival Skills Part II On the Water Chapter 6. Kayaking Techniques, Strokes, and Maneuvers Chapter 7. Sea Kayaking Chapter 8. River and Whitewater Kayaking Chapter 9. Pursuing Paddlesports-Pass It On
Keywords: Kanosport